2016
DOI: 10.1007/s12678-016-0319-9
|View full text |Cite
|
Sign up to set email alerts
|

Co-sputtered PtxPdyAlz thin film electrocatalysts for the production of hydrogen via SO2(aq) electro-oxidation

Abstract: A co-sputtered Pt x Pd y Al z ternary system was investigated for potential use as anode catalyst for the electrooxidation of aqueous sulphur dioxide (SO 2 ), a key reaction in the hybrid sulphur (HyS) process for splitting water into hydrogen and oxygen. Combining the noble metals Pt and Pd with Al resulted in no significant improvement in onset potential; however, current output was improved for the majority of the electrocatalysts evaluated. Of these electrocatalysts, only a single ternary composition exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…The next step in their research was to add a non-noble metal, aiming better catalyst activity and a lower price. Falch et al [41] developed a film composed of platinum, palladium and aluminium, which are co-sputtered on a support. They made improvements on the onset potential and in current density, obtaining 396.73 mA/mgPt with the ternary combination Pt 40 Pd 57 Al 3 .…”
Section: Combination Of Platinum With Other Metalsmentioning
confidence: 99%
“…The next step in their research was to add a non-noble metal, aiming better catalyst activity and a lower price. Falch et al [41] developed a film composed of platinum, palladium and aluminium, which are co-sputtered on a support. They made improvements on the onset potential and in current density, obtaining 396.73 mA/mgPt with the ternary combination Pt 40 Pd 57 Al 3 .…”
Section: Combination Of Platinum With Other Metalsmentioning
confidence: 99%
“…Pt (1768°C) and Pd (1555°C) are expected to be the least influenced by the annealing temperature of 900°C, which is well below the melting point of these two metals. However, as part of a previous investigation into this metal combination, an XPS analysis revealed that a degree of alloy formation occurs between Pt and Al and that contraction of the thin film also occurs [11]. This occurrence of contraction (exposure of the GC) is supported by the different degrees of agglomeration of the thin films as observed by the SEM analysis (Fig.…”
Section: Semmentioning
confidence: 72%
“…Trend (b) is an indication that, in terms of current output, the annealing treatment has no significant effect on increasing the current output of the respective films, which may suggest that no migration of a specific metal to the surface of the thin film occurred [11], i.e. the exposed AN surfaces available for SO 2 electro-oxidation have the same surface composition as the AD films.…”
Section: Electrochemical Performancementioning
confidence: 99%
See 2 more Smart Citations